2003
DOI: 10.1046/j.1526-4610.2003.03085_7.x
|View full text |Cite
|
Sign up to set email alerts
|

Contrasts in cortical magnesium, phospholipid and energy metabolism between migraine syndromes.

Abstract: Neurology. 2002;58:1227‐1233. BACKGROUND: Previous single voxel (31)P MRS pilot studies of migraine patients have suggested that disordered energy metabolism or Mg(2+) deficiencies may be responsible for hyperexcitability of neuronal tissue in migraine patients. These studies were extended to include multiple brain regions and larger numbers of patients by multislice (31)P MR spectroscopic imaging. METHODS: Migraine with aura (MWA), migraine without aura (MwoA), and hemiplegic migraine patients were studied be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(59 citation statements)
references
References 0 publications
2
55
0
2
Order By: Relevance
“…Most of these studies suggested a metabolic disturbance in the brain of MwA patients and, to a lesser extent, of MwoA patients, which is evident even in the interictal period [10][11][12][13][14][15][16][17][18]. In MwoA, 1 H-MRS has only been performed following visual stimulation and using relative quantification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of these studies suggested a metabolic disturbance in the brain of MwA patients and, to a lesser extent, of MwoA patients, which is evident even in the interictal period [10][11][12][13][14][15][16][17][18]. In MwoA, 1 H-MRS has only been performed following visual stimulation and using relative quantification.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis is that migraine is a disorder that might be caused by the concurrence of two pathophysiological components: excessive cortical activation due to lack of habituation during repetitive stimulation as well as a decreased brain mitochondrial energy reserve [8,9]. In the last 20 years several magnetic resonance spectroscopy (MRS) studies, in particular phosphorus magnetic resonance spectroscopy ( 31 P-MRS), suggested an energy disturbance in the brain of migraine patients during interictal periods [10][11][12][13][14][15][16][17][18]. Recent studies emphasized more on proton magnetic resonance spectroscopy ( 1 H-MRS) with a lot of heterogenous, sometimes contradictory, results (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that it could be the expression of a reduced inhibition consequent upon GABAergic system deficiency in occipital cortex [29,30]. Furthermore, insufficient glutamatergic function [31], mutations in the presynaptic calcium [32], low brain magnesium levels [33] and an abnormal mitochondrial energy metabolism [34][35][36] may also be involved.…”
Section: Electrophysiological Studymentioning
confidence: 99%
“…MRS studies have shown low phosphocreatine, high adenosine 5'-diphosphate, and low phosphocreatine:Pi ratios in patients with migraine. These findings have raised the question of whether there is a subset of migraine patients with mitochondrial energy defect [35].…”
Section: New Imaging Techniques In Migrainementioning
confidence: 99%